2004
DOI: 10.1002/em.20045
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between cagA, vacA, and iceA genotypes of Helicobacter pylori and DNA damage in the gastric mucosa

Abstract: Helicobacter pylori (H. pylori) is believed to predispose carriers to gastric cancer by inducing chronic inflammation. The inflammatory processes may result in the generation of reactive oxygen and nitrogen species that damage DNA. In this study, we investigated the relationships between DNA damage in the gastric mucosa and cagA, vacA, and iceA genotypes of H. pylori. The study was conducted with biopsies from the gastric antrum and corpus of 98 H. pylori-infected and 26 uninfected control patients. H. pylori … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 39 publications
3
16
0
1
Order By: Relevance
“…Our results demonstrate increased levels of oxidative DNA damage in patients infected with cagA + strains. The importance of this oxidative DNA damage has been confirmed by our previously study [7] and by study of Farinati et al [31], that also reported higher levels of oxidative DNA damage in H. pylori-infected patients by cagA + strains. These results may be explained by the continuous induction of DNA damage in the gastric mucosa caused by persistent generation of ROS and RNS in inflammatory processes, and the accumulation of DNA damage due to the inhibition of DNA repair and apoptosis by nitric oxide [32].…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Our results demonstrate increased levels of oxidative DNA damage in patients infected with cagA + strains. The importance of this oxidative DNA damage has been confirmed by our previously study [7] and by study of Farinati et al [31], that also reported higher levels of oxidative DNA damage in H. pylori-infected patients by cagA + strains. These results may be explained by the continuous induction of DNA damage in the gastric mucosa caused by persistent generation of ROS and RNS in inflammatory processes, and the accumulation of DNA damage due to the inhibition of DNA repair and apoptosis by nitric oxide [32].…”
Section: Discussionsupporting
confidence: 62%
“…However, this association varies considerably across populations and the scientific evidence is somewhat inconsistent [27]. In the previous study, we investigated the relationships between DNA damage in the gastric mucosa and cagA, vacA, and iceA genotypes of H. pylori without use of enzymes endo III and FPG [7]. Endo III recognizes oxidized pyrimidines, while FPG identifies oxidized purines, especially 8-oxo-guanine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…pylori is genetically diverse and type I strains, which are cagA 1 and secrete the vacuolating cytotoxin, are assumed to be the most virulent (61,62) , being associated with the presence of more severe disease (63)(64)(65)(66)(67)(68)(69) . Increased bacterial load could also promote gastric inflammation (70) which therefore could stimulate epithelial damage and increase disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…On the host side, Ladeira et al (23,24) investigated the extent of DNA damage in normal and infected gastric tissue using a single-cell comet assay. They found that DNA damage correlated with H. pylori infection and degree of gastritis.…”
Section: H Pylori Virulence Factors and Their Modulation Of Host Celmentioning
confidence: 99%